The Effects of Paeonia lactiflora Pall. and Astragalus Membranaceus Single Extracts on Bone Metabolic Profile in Ovariectomized Mice - Min Jung Park; Cha Soon Kim; Ki-Tae Ha; Ju-Hwa Baek; Hyewon Cho; Youngeun Lee; Chang-Woon Kim; Bo Sun Joo (Clinical and Experimental Obstetrics & Gynecology)
Background: Metabolic bone disease, associated with estrogen deficiency, is common condition in postmenopausal women. Paeonia lactiflora Pall. (PL) and Astragalus membranaceus (AM) have been known to have estrogenic activity and to improve postmenopausal osteoporosis symptoms when used as a mixture with other herbs. However, there have been no comparative studies on the effects of PL and AM on the bone metabolic profile. Thus, the present study aimed to investigate the effects of the single extracts of PL and AM on bone and metabolic profile, and further to compare the effects of the two herbs. Method: A total of 70 mice were randomly divided into seven groups (n = 10): six groups were bilaterally ovariectomized (OVX) and one group served as a sham-operated control (Sham). Two OVX groups received PL at 23.5 (OVX-PL-L) and 47 (OVX-PL-H) mg/kg bw/day. Another two OVX groups received AM at 38.5 (OVX-AM-L) and 77 (OVX-AM-H) mg/kg bw/day. The remaining two groups served as positive and negative controls and received estradiol valerate (OVX-E2) and distilled water (OVX-vehicle). Vehicle (distilled water), PL, AM, and E2 were administered to mice by oral gavage once a day for 6 weeks at a volume of 10 mL/kg of body weight. The body and uterine weights, serum lipid profiles, osteocalcin levels, and biomarkers of bone formation were measured. The expressions of the genes associated with the estrogen receptor (ER)-related downstream pathway were examined in the Michigan Cancer Foundation-7 (MCF-7) cells. Results: Treatment with PL and AM reversed OVX-induced body weight gain and changes to serum triglyceride, estradiol and osteocalcin levels at both doses. Evaluation of bone formation revealed that low-dose (23.5 mg) PL resulted in improvements in bone mineral density (BMD) and bone volume fraction (BV/TV), whereas AM improved all bone formation related parameters, BMD, BV/TV, trabecular number (Tb.N), and trabecular thickness (Tb.Th) at a high dose. There was no significant difference in the effects of PL and AM on changes in body weight and BMD, but high-dose AM was more effective than PL in restoring changes in osteocalcin levels and formation of the trabecular bone structure. Both PL and AM increased extracellular signal-regulated kinase and protein kinase B in MCF-7 cells. Conclusions: These results suggest that both low-dose PL and high-dose AM can be effective herbal alternatives to inhibit body weight gain and improve bone metabolism. This effect was more pronounced with AM than with PL.